Effects of extensive reading on Malaysian Form Four students' reading comprehension, vocabulary acquisition, attitude and motivation - M. Kulasingam, Anna Nirmala (2013)
The purpose of the study is to determine the effects of Extensive Reading (ER) on reading comprehension of learners and also whether reading extensively will help in learners’ vocabulary acquisition of texts. The study also aims to investigate the effects of Extensive Reading on learners’ attitude towards reading in English and their motivation for learning English Language. The subjects were 89 Form Four students from a school in Klang. The study employed a Solomon three-group design using 31 students as the experimental group and 58 students as the control groups, of which one control group was excluded from the pretest to separate the effects caused by using the same instruments. A combination of both quantitative and qualitative methods was used in the data collection, in order to consolidate the findings. Descriptive statistics for the reading comprehension and vocabulary gains in the pretest and posttest after the treatment were reported, followed by the testing of the research hypotheses using Analysis of Variance procedure (ANOVA, SPSS 20.0). Next, attitude and motivation questionnaires administered at the end of this experimental study were analysed. The first questionnaire was focused on the students' attitudes toward Extensive Reading and the second on the motivation for learning English Language. Then, parametric tests, Paired t-tests was run by the Statistical Package for Social Sciences (SPSS) version 20.0 for both domains to determine whether there was any significant difference between the groups in their attitude towards Extensive Reading and their motivation for learning English. Lastly, a reading log was given to each student and they were instructed to complete a separate reading log for each graded reader. These were completed and handed in each week, depending on the length and difficulty of the text. Then the responses were collected and tabulated and analysed using a Frequency Table. From the results of the study, there was a significant difference between the three groups in the reading comprehension and vocabulary acquisition posttest scores This shows that the participants had positive gains in reading comprehension and vocabulary acquisition. Next, there was a significant difference in the vocabulary test in the posttests. This shows that the participants had positive gains in vocabulary acquisition. Participants also displayed positive attitudes toward Extensive Reading and learning English and have both instrumental and integrative motivation for learning the language. Above all, the majority of students expressed a sense of accomplishment at the end of the programme and felt they became more confident readers through completing an entire English book without using a dictionary. This feeling boost their motivation to read even more. Thus, the results provide support for integrating Extensive reading into the English curriculum for improving current learning and teaching approaches. The results of the current study also suggest that using Extensive reading in a secondary school English curriculum is feasible and effectual in improving reading comprehension and vocabulary acquisition and even enhancing students' reading motivation and attitude.